Tecnologia de aplicação aérea e terrestre na cultura da batata - Bueno, Mariana Rodrigues (2011)
Potato is the main vegetable cultivated in Brazil, however, this crop shows great problems concerning to pesticide application technology. These high frequency of product application, specially fungicides, is responsible for increasing the costs of production. Therefore, it is necessary to study methods that may optimize the technology by which pesticides are applied, aiming to associate efficiency, economic viability and environmental safety. This research was divided into two parts: the first one was done in a laboratory, in a completely randomized design. By the laser diffraction technique, the droplet spectrum produced by two air induction twin flat-fan nozzles (AD-IA/D 11002 e AD-IA/D11004) and two hollow-cone nozzles (MAG - 2 e MAG - 4) was evaluated, in factorial design 3 x 2: three spray pressures (207, 276 and 345 kPa for twin flat-fan nozzles, and 414, 483 and 552 kPa for cone nozzles); and two spray liquid compositions (water and water with phosphatydilcoline + propionic acid adjuvant). The second part of this work was conduct in field, in duplicate, in a commercial potato tillage, in a completely randomized design, in factorial 6 x 2: six application forms (aerial with rotative atomizer at 15 and 30 L ha-1 and ground at 200 and 400 L ha-1 with air induction twin flat-fan and hollow-cone nozzles) and two spray liquid compositions (water and water with phosphatydilcoline + propionic acid adjuvant). Deposition, run off and drift of the spray liquid in the potato crop were evaluated by spectrophotometry technique, while the droplet spectrum was obtained by image analysis of water-sensitive papers. After the laboratory study, one could conclude that the adjuvant addition reduced the volume median diameter for the AD-IA/D 11002 and 11004 nozzles. However, it had an opposite effect with the MAG - 4 nozzles and did not change with the MAG - 2 nozzles. In adverse weather conditions, it is not recommended to use hollow cone spray nozzle, even if the adjuvant is added because the high potential risk of drift. The field evaluations showed that, in general, the adjuvant addition provided a better spray liquid retention on lower and upper leaves. The decrease of spray volume, provided a good spray liquid deposition on target, and it is an alternative for cost reduction and operational capacity increase. The aerial application was as efficient as the ground applications on the spray liquid deposition on target. The smaller droplet sizes and relative spans were produced by aerial application; however, the larger droplet diameters and the less percentage of spray volume in droplets smaller than 100 μm diameter were obtained with the use of air induction twin flat-fan nozzle.